Setting expectations following endoscopic cubital tunnel release - Cobb, Tyson K. (Springer US, 2014)
BACKGROUND: The objective was to evaluate recovery characteristics of patients undergoing endoscopic cubital tunnel release (ECuTR) by determining the following: (1) return to work (RTW) times following ECuTR compared with RTW times of patients that underwent anterior transposition of the ulnar nerve (ATUN), (2) satisfaction rates and factors affecting satisfaction, (3) resolution rates of common preoperative complaints and findings, and (4) effect of preoperative ulnar nerve subluxation on postoperative outcomes. METHODS: A total of 172 cases in 148 patients undergoing ECuTR were prospectively enrolled including 56 women and 92 men. Kaplan-Meier analyses were performed to determine RTW time for ECuTR patients and for a cohort of 15 patients that underwent ATUN. Patients were evaluated for subjective and objective complaints preoperatively and postoperatively. Cases were grouped by Dellon’s classification preoperatively and modified by Bishop’s postoperatively. RESULTS: Half of ECuTR patients returned to normal work within 8 days postoperatively versus 71 days following ATUN. Variables significantly negatively affecting RTW were male sex, manual labor, and worker’s compensation status. Dellon’s was the best predictor of postoperative satisfaction. Complete resolution of symptoms occurred in 86 % of patients for weakness, 81 % for pain, 79 % for numbness and tingling (N/T), 78 % for atrophy, 76 % for abnormal two-point discrimination, and 65 % for Wartenberg’s. Preoperative ulnar nerve subluxation had no effect on outcome. CONCLUSIONS: Improved RTW time following ECuTR versus ATUN indicates potential and substantial cost-saving implications with respect to reduced worker productivity loss. Patients with more severe preoperative Dellon’s classification can expect less optimal results regarding postoperative satisfaction and resolution rates of N/T and pain.